Thor : tales of Asgard,. To the death! - Lee, Stan. 1922-2018 (Spotlight, a division of the ABDO Group, 2014)
"An adaptation, in graphic novel form, of comic books revealing the adventures of the Norse gods and Thor before he came to Earth, featuring a battle between the godling and his friends and the evil ruler, Mogul"--Publisher.